Penerapan Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam - Nelly (Jurnal Pendidikan Agama Islam, 2024)
As part of the post-pandemic recovery of online learning, the Ministry of Education and Culture officially launched a modern curriculum entitled "Freedom to Learn" which will be implemented independently in all educational units starting in the 2022/2023 academic year. The purpose of this research is to determine the positive impacts and obstacles to implementing an independent curriculum for learning Islamic religious education at SMP Negeri 3 Sidikalang and implementing an independent curriculum for learning Islamic religious education at SMP Negeri 3 Sidikalang. This research applies a qualitative phenomenological approach with a type of field research. Data collection techniques were carried out through observation, interviews and document study. Based on research findings, the independent process of curriculum implementation is divided into three stages: planning, implementation, and evaluation. The positive impacts of implementing an independent curriculum in Islamic religious education learning include increasing teacher and student creativity, increasing student enthusiasm and activeness in learning, and increasing teacher enthusiasm in developing their own skills. The obstacle to implementing the unique Islamic religious education curriculum is that educators are unable to provide fun, high-quality learning, and determine topics and content for P5 activities that suit students' interests and talents.